The good gift of weakness God's strength made perfect in the story of redemption - Schumacher, Eric (Eugene, Oregon Harvest HousePublishers, 2024)
"Weak by design. Our culture deifies strength--and sadly, the church does too. Who has the most successful ministry, the largest congregation, or the godliest family? Our misplaced faith in human strength is a false hope with no basis in Scripture. A closer look through the Bible reveals the central role human frailty plays in the redemption story, From Genesis to Revelation, God's power is made perfect when people are at their weakest. Far from an undesirable defect, God designed our weakness to draw us closer to himself. As you learn to accept the good gift of weakness, you will experience true strength--the kind that only comes from a loving and infinitely powerful God."--Page [4] of cover
Weakness in the new creation.
Includes bibliographical references
Keywords: Jesus Christ -- Crucifixion; Jésus-Christ - Crucifiement; Trust in God -- Religious aspects; Faith -- Religious aspects; God (Christianity); Christian Life; Confiance en Dieu - Aspect religieux; Foi - Aspect religieux; Dieu (Christianisme); Vie chrétienne